Sistem Peringatan Dini untuk Mendeteksi Lifetime Sparepart pada Mesin TR OSAWA - Adi Nugroho; Yahri Nastangin (Jurnal Optimasi Sistem Industri, 2017)
Maintenance is a very important activity to keep an equipment always at its best condition. This research aims to create an early warning system/ lifetime spare parts detector of Nissin Kogyo Batam (NKB)Company’sTR Osawa machine by adopting PLC (Programmable Logic Controller). PLC is used to automatically calculate the lifetime spare parts of TR Osawa machine. PLC will shut down the machine if it detects that lifetime spare parts have reached the specified setting standard (380-400 k pcs). As a result, PLC machine can provide more accurate results than manual counting.